PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU DIMEDIASI DENGAN KOMITMEN ORGANISASIONA ( Studi pada guru SD Negeri di UPTD Pendidikan Kecamatan Genuk Semarang) - Riyanti, Riyanti (Students Journal of Economic and Management, 2012)
This research is aimed to test and analyze the influence of motivation and job satisfactory towards teacherâs working mediated with organizational commitment of the teacher ofÂ  s State Elementary School in â UPTD Kecamatan Genuk Semarangâ, with 146 respondences. The technique of collecting data used is random samplimh by giving a austioner to the respondences. This research is aimedÂ Â Â  to: 1)Analyze the influence of motivation towards organisational commitment , 2) AnalyzeÂ  the job satisfactory towards organizational commitment, 3) Analyze the influence of motivation towards teacherâs working, 4) Analyze the influence of satisfactory towardsÂ  teacherâs working, 5) Analyze the influence of organizational commitment towards teacherâs working, 6) Analyze and prove the organizational commitment as an influence of motivation â mediation towardsÂ  teacherâs working, 7) Analyze and prove organisational commitment as an influence of working satisfactoryâs mediation towards teacherâs working. The technique of testing data which is used in this research includes validity with factor analysis and reliability testbyCronbachs alpha formula, multiple regression analysis, tests of significance and coefficient of determinationto prove thetruth ofthe hypothesisof the study,as well astestingthe effect ofmediation. The result of the research showed that: 1). Motivation didnât influence positively towards organizational commitment, 2). Job satisfactory influences positively and significantly towards organizational commitment, 3). Motivation influences positively and cantly towards teacherâs working, 4).Job satisfactory didnât influencedirectly towarde teacherâs working, 5)OrganizationalCommitment influence positive andsignificanteffecton the performance ofteachers witha positivebetaand significancepricesbelowarerequired. 6)organizationalcommitmentdid notmediate theeffect ofwork motivation, whilework motivationdirectly affects theperformance of teachers. 7)Organizationalcommitmentmediates theinfluence ofjob satisfactory towards teacherâs working. Keywords: Motivation, Job Satisfactory, OrganizationalCommitmentaÂ  working